2021
DOI: 10.1038/s41477-021-00848-7
|View full text |Cite|
|
Sign up to set email alerts
|

Ancient genomes reveal early Andean farmers selected common beans while preserving diversity

Abstract: Introductory paragraphAll crops are the product of a domestication process that started less than 12,000 years ago from one or more wild populations [1,2]. Farmers selected desirable phenotypic traits, such as improved energy accumulation, palatability of seeds and reduced natural shattering [3], while leading domesticated populations through several more or less gradual demographic contractions [2,4]. As a consequence, erosion of wild genetic variation [5] is typical of modern cultivars making them highly sus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 61 publications
2
22
0
5
Order By: Relevance
“…There was three-fold greater genetic diversity reduction in the Mesoamerican gene pool compared to the Andean gene pool [33]. Very recently Trucchi et al [34], investigated the temporal dynamics of genetic diversity and selection throughout the domestication process of the common bean in the southern Andes. It was reported that the genomic variation of the pool of cultivars from different Andean regions is higher than the pool of ancient seeds from the central-western and north Argentina.…”
Section: Common Bean Origin and Domesticationmentioning
confidence: 99%
“…There was three-fold greater genetic diversity reduction in the Mesoamerican gene pool compared to the Andean gene pool [33]. Very recently Trucchi et al [34], investigated the temporal dynamics of genetic diversity and selection throughout the domestication process of the common bean in the southern Andes. It was reported that the genomic variation of the pool of cultivars from different Andean regions is higher than the pool of ancient seeds from the central-western and north Argentina.…”
Section: Common Bean Origin and Domesticationmentioning
confidence: 99%
“…In short, ML [138,[176][177][178][179] and deep learning approaches [133,170,180,181] promise assisting the conservation [102,[182][183][184], managing [185,186], prioritization [187][188][189], and introgression [190,191] of crop wild variation from genebanks (Figure 2). ML may be particularly useful in unexplored isolated pockets of diversity, which contain allelic variants otherwise eroded from modern genotypes [192,193].…”
Section: Geavs Geavsmentioning
confidence: 99%
“…Genomic information is an important breeding tool to improve selection accuracy and to accelerate genetic gain in beans (Delfini et al., 2021; Diaz et al., 2021; Keller et al., 2020). However, selection for desirable traits also results in erosion of genetic diversity (Esquinas‐Alcázar, 2005; Trucchi et al., 2021) and inefficient selection procedures in crop breeding may lead to premature plateauing of genetic gain (Cowling et al., 2017). The rate of erosion of genetic diversity in breeding programs may be reduced and selection efficiency improved through optimal contributions selection (OCS), which balances genetic gain against loss in genetic variation (Cowling et al., 2017, 2019; Gorjanc et al., 2018; Kinghorn, 2011; Kinghorn & Kinghorn, 2021; Woolliams et al., 2015).…”
Section: Introductionmentioning
confidence: 99%